2020
DOI: 10.1002/ncp.10614
|View full text |Cite
|
Sign up to set email alerts
|

Increased Association With Malnutrition and Malnourishment in Older Adults Admitted With Hip Fractures Who Have Cognitive Impairment and Delirium, as Assessed by 4AT

Abstract: Increased association with malnutrition and malnourishment in older adults admitted with hip fractures with cognitive impairment and delirium, as assessed by 4AT. Nutrition in Clinical Practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…The same MUST protocol was used by all four hospitals to identify patients at risk of malnutrition. [21][22][23] The information for MUST was recorded routinely by healthcare professionals during hospital admission. This procedure comprises three independent variables: body mass index (BMI [calculated as weight in kilograms divided by height in meters squared]) score (BMI > 20.0 = 0, BMI 18.5-20.0 = 1, and BMI < 18.5 = 2), unplanned weight loss in the previous 3-6 months (weight loss < 5% = 0, weight loss 5-10% = 1, and weight loss > 10% = 2), and acute disease effect score (a score of 2 was added if a patient was recently affected by a disease and there was no nutrition intake or likely to be no nutrition intake for >5 days).…”
Section: Nutrition Statusmentioning
confidence: 99%
“…The same MUST protocol was used by all four hospitals to identify patients at risk of malnutrition. [21][22][23] The information for MUST was recorded routinely by healthcare professionals during hospital admission. This procedure comprises three independent variables: body mass index (BMI [calculated as weight in kilograms divided by height in meters squared]) score (BMI > 20.0 = 0, BMI 18.5-20.0 = 1, and BMI < 18.5 = 2), unplanned weight loss in the previous 3-6 months (weight loss < 5% = 0, weight loss 5-10% = 1, and weight loss > 10% = 2), and acute disease effect score (a score of 2 was added if a patient was recently affected by a disease and there was no nutrition intake or likely to be no nutrition intake for >5 days).…”
Section: Nutrition Statusmentioning
confidence: 99%
“…This study also included risk of malnutrition, particularly amongst those with delayed swallow screening, prolonged LOS on HASU and TRC, which has not previously been well-documented. Malnutrition amongst patients admitted with an acute stroke is a significant indicator of post-stroke adverse outcomes including disability, mortality and prolonged LOS [ 16 ]. Few studies have also reported LOS; our observation of a median LOS on HASU of 18 and 6.5 days respectively for HOS and COS patients is very similar that of 17 and 8 days by Saltman et al [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Initially, the patient was given three spoons of water, and if there was no risk of aspiration, the patient was challenged with one cup of water. If successful, a trial was continued with a soft-diet meal [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, researchers highlighted the role of coexisting geriatric syndromes, including cognitive impairment and delirium among older adults hospitalized with hip fractures. They assumed a strong correlation between delirium, cognitive impairment, and malnutrition [ 32 ].…”
Section: Falls and Fractures—consequences Of Malnutritionmentioning
confidence: 99%